2011
DOI: 10.1007/s11325-011-0587-9
|View full text |Cite
|
Sign up to set email alerts
|

Complete denture wear during sleep in elderly sleep apnea patients—a preliminary study

Abstract: Contrary to previous studies, we found that OSA patients may experience more apneic events if they sleep with their dentures in place. Specifically, in mild OSAS patients, the use of dentures substantially increases the AHI especially when in the supine position.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1
11

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 38 publications
1
22
1
11
Order By: Relevance
“…Similarly, ARISAKA et al [63] found that wearing dentures during sleep improved the apnoeas and hypopneas in 70% of individuals but interestingly, 14% showed a significant increase in the AHI while wearing dentures. This controversial aspect was confirmed by ALMEIDA et al [64], who conducted a randomised trial and found an aggravation of OSA while wearing dentures. This worsening of OSA was predominantly related to individuals with mild OSA sleeping in the supine position [64].…”
Section: Denture Wearing At Nightmentioning
confidence: 87%
See 1 more Smart Citation
“…Similarly, ARISAKA et al [63] found that wearing dentures during sleep improved the apnoeas and hypopneas in 70% of individuals but interestingly, 14% showed a significant increase in the AHI while wearing dentures. This controversial aspect was confirmed by ALMEIDA et al [64], who conducted a randomised trial and found an aggravation of OSA while wearing dentures. This worsening of OSA was predominantly related to individuals with mild OSA sleeping in the supine position [64].…”
Section: Denture Wearing At Nightmentioning
confidence: 87%
“…This controversial aspect was confirmed by ALMEIDA et al [64], who conducted a randomised trial and found an aggravation of OSA while wearing dentures. This worsening of OSA was predominantly related to individuals with mild OSA sleeping in the supine position [64].…”
Section: Denture Wearing At Nightmentioning
confidence: 87%
“…Minimal or no carry-over effect is expected based on the action of the postulated mechanism of intervention [28] (additional analyses of raw data from research team member FRA: Grizzle’s model [43] sequence effect P  = 0.8, period effect P  = 0.9, intervention effect P  = 0.002). Therefore, no wash-out period was deemed necessary.
Figure 1 Trial design.
…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the literature suggests that there is a possible association between sleep disturbance and wearing a complete denture during sleep, which may explain the mechanism underlying the relationship between obstructive sleep apnea and edentate individuals [26, 27]. One hypothesized effect was that the use of a denture during sleep may lead to open bite and mouth breathing with a decrease in the tone of the pharyngeal muscles, thus leading to the development or worsening of obstructive sleep apnea [28]; an alternative hypothesis holds that sleep quality and pharyngeal patency are maintained by nocturnal denture use. Moreover, this denture effect appears to be different between healthy edentate older people and those with sleep disturbances [29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation